To what extent are knowledge-intensive business services contributing to manufacturing? A subsystem analysis - Daria Ciriaci; Daniela Palma (European Commission, Joint Research Centre (JRC), 2012)
The rise of knowledge-intensive business services (KIBS) may be considered as one of the decisive trends of economic evolution of industrialised countries in recent decades. This paper uses the concept of vertical integrated sectors and the subsystem approach to input-output matrix analysis to study the vertical integration of knowledge-based business services into manufacturing sectors. To date, companies increasingly rely on outside innovation for new products and processes and have become more active in licensing and selling results of their innovation to third parties. At the same time, they may rely on the marketing and financial consulting offered by third parties. As a consequence, considering manufacturing and KIBS as vertically inter-related sectors, the hypothesis of a virtuous circle can be expressed in the following way: the higher the degree of integration between KIBS and manufacturing sectors along what we could define as a `knowledge-based value chain', the easier the knowledge diffusion and the competitiveness of the economic system as a whole. The study covers Germany, France, Italy, and the United Kingdom over the period 1995-2005. Results decisively support both the existence of structural differences among the countries considered, and a significant heterogeneity to the extent to which manufacturing outsources to knowledge-intensive business services.
Keywords: L60; L84; O33; O32; P00; 330; Knowledge-intensive business services; subsystem approach; input-output analysis; knowledge diffusion